UKRAINIAN POLITICAL ELITE: SOCIAL EFFECTIVENESS ASSESSMENT BY DOMESTIC SCIENTISTS - Bilous, L. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2018)
The article deals with the analysis of domestic scientists` research on the Ukrainian political elite social effectiveness and provides the coverage of their activity assessment in terms of publicinterests realization. It is noted that among the numerous works of domestic scientists on the consideration of certain aspects of the Ukrainian political elite formation and functioning processes there are A. Pakhariev`s, F. Rudych`s, O. Hladkyi`s, M. Holovatyi`s, M. Shulha`s, M. Mykhailychenko`s, I. Pobochii`s, Y. Shaihorodskyi’s and many other`s researches where the matter is raised. It is noticed that the scientists mainly negatively evaluate the political elite`s social activity in the period of Ukrainian independence. They emphasize that the “formal” political elite, “pseudoelite” of Ukraine is not solid and cohesive. They are not capable of thinking strategically and on a large scale, they are not ready to take historical responsibility for the society`s fate as a whole, adequately protect national interests, fight against corruption and, in general, resolutely carry out reforms. Domestic scientists emphasize that the Ukrainian political elite in their activity are still motivated mainly by their own narrow business interests, but not the interests of the society and the state. The article suggests that the political elite social activity negative assessment bythe domestic scientists is a general theoretical reflection of people`s real distrust of the Ukrainian authority because of political crisis, corruption, low salaries and high prices, inflation, forced emigration abroad, the conflict in the East and so on as various opinion polls show. The analysis of the scientific researches on our country`s political elite social effectiveness assessment has also made it possible to single out the scientists` vision of certain conditions under which a successful fulfillment of the elite`s social transformation subject function is possible.